KADAR NITROGEN PADA SPESIMEN FESES ORANG DEWASA NORMAL (NON INFEKSI STH): Nitrogen pada spesiemen feces orang dewasa - darmadi - adi; Siti juariah; Windi Aprilya Saputri (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Nitrogen is a very important element for organisms. Nitrogen in the body is also an element that has a very large role in the formation of proteins, which are the main compounds in organisms. All forms of compounds in the body, metabolic waste will be excreted in the form of feces. Feces are expelled from the human body through the anus as waste material from the digestive process of food along the digestive tract system. The purpose of this study was to determine normal levels of nitrogen in feces. The method used in this research is a laboratory experiment. Testing for nitrogen levels is done by checking the nitrogen levels in normal feces (not infected with STH). The results showed that the nitrogen content in the feces of sample A was 0.19%, in sample B the nitrogen content was 0.24%, and the nitrogen content in sample C was 0.25%. From this study, it was obtained that the average nitrogen content in normal feces in adults was 0.22%. Keywords: Nitrogen, Normal Stool, Adults, non sth . infection